Seg1 controls eisosome assembly and shape - Moreira, Karen E.; Schuck, Sebastian (The journal of cell biology, 2012)
Eisosomes are stable domains at the plasma membrane of the budding yeast Saccharomyces cerevisiae and have been proposed to function in endocytosis. Eisosomes are composed of two main cytoplasmic proteins, Pil1 and Lsp1, that form a scaffold around furrow-like plasma membrane invaginations. We show here that the poorly characterized eisosome protein Seg1/Ymr086w is important for eisosome biogenesis and architecture. Seg1 was required for efficient incorporation of Pil1 into eisosomes and the generation of normal plasma membrane furrows. Seg1 preceded Pil1 during eisosome formation and established a platform for the assembly of other eisosome components. This platform was further shaped and stabilized upon the arrival of Pil1 and Lsp1. Moreover, Seg1 abundance controlled the shape of eisosomes by determining their length. Similarly, the Schizosaccharomyces pombe Seg1-like protein Sle1 was necessary to generate the filamentous eisosomes present in fission yeast. The function of Seg1 in the stepwise biogenesis of eisosomes reveals striking architectural similarities between eisosomes in yeast and caveolae in mammals.
Gesehen am 06.11.2018